2018
DOI: 10.1111/poms.12909
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Distribution Strategy for Enterprise Software: Retail, SaaS, or Dual Channel?

Abstract: While the optimal distribution channel strategy of physical goods has been extensively studied, there is a lack of research for that of enterprise software as a digital good. This research analyzes the optimal distribution strategy of enterprise software by taking into account the distinct features of enterprise software for both the short‐run problem, in which the software quality is fixed, and the long‐run problem, in which the software quality becomes part of the strategic decisions. Our results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…However, one distinct feature of these markets lie in that they don't rely on revenues from advertisements as the digital music market. Therefore, previous literature usually focuses on deterioration of cars (Desai and Purohit 1998), software's upgrade (Jia et al 2018), customization (Li et al 2018), or eBook readers re-lending options (Chen and King 2017) when examining the subscription model of software and eBook. We analyze how revenues from advertisements impact the music provider's choice of pricing models.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…However, one distinct feature of these markets lie in that they don't rely on revenues from advertisements as the digital music market. Therefore, previous literature usually focuses on deterioration of cars (Desai and Purohit 1998), software's upgrade (Jia et al 2018), customization (Li et al 2018), or eBook readers re-lending options (Chen and King 2017) when examining the subscription model of software and eBook. We analyze how revenues from advertisements impact the music provider's choice of pricing models.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…A significant finding of our research is that in the relatively secure environment, the firm is suggested to exclude the on-premise strategy from releasing products, which is different from what was proposed in Li et al (2017Li et al ( , 2018. The main reason is that the decrease of potential loss from security risks ωα effectively benefits the market expansion of SaaS even under the negative externality.…”
Section: Discussionmentioning
confidence: 73%
“…However, with the advent of high-speed broadband access, cloud service has become widely acknowledged, rapidly changing how software is delivered (Guo and Ma, 2018). Many well-established software firms release cloud-based versions of their existing products, making software-as-aservice (SaaS) appear and become another crucial versioning strategy (Li et al, 2018).…”
Section: Imds 1223 592mentioning
confidence: 99%
“…Xu (2009) study a joint pricing and product quality decision problem in a distribution channel, Numerical experiments (Hua et al, 2011a(Hua et al, , 2011b find that the revenue-sharing contract can perfectly coordinate the distribution channel in the product design problem. The detailed topic has also become part of distribution channel literature where people pay more attention (Li et al, 2018;Saha et al, 2018;Xiao, 2019;Farham-Nia and Ghaffari-Hadigheh, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%